2019
DOI: 10.3390/nu11050991
|View full text |Cite
|
Sign up to set email alerts
|

Spilanthol from Traditionally Used Spilanthes acmella Enhances AMPK and Ameliorates Obesity in Mice Fed High-Fat Diet

Abstract: Spilanthol (SP) is a bioactive compound found in Spilanthes acmella, giving the flowers and leaves a spicy taste. Studies found that phyto-ingredients stored in spice plants act against obesity-related diseases. SP has antimicrobial, anti-inflammatory, and analgesic properties, but the effects on obesity are not yet known. We investigated the effects of SP in differentiated adipocytes (3T3-L1 cells) and mice fed a high-fat diet (HFD). SP significantly inhibited intracellular lipid accumulation and significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The results of the current study are also consistent with those of our previous in-vitro study [ 18 ], in which NF was found to activate SREBP-1/2 and suppress AMPK, leading to lipogenesis and lipid accumulation. An interesting study using HFD mice showed that upregulated AMPK inhibited lipogenic and adipogenic transcriptional factors [ 22 ]. Furthermore, a high-energy status, such as that occurring in obesity, and calcium channel blockers, such as NF, may induce a low active form of AMPK (p-AMPK), thereby reducing energy production.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study are also consistent with those of our previous in-vitro study [ 18 ], in which NF was found to activate SREBP-1/2 and suppress AMPK, leading to lipogenesis and lipid accumulation. An interesting study using HFD mice showed that upregulated AMPK inhibited lipogenic and adipogenic transcriptional factors [ 22 ]. Furthermore, a high-energy status, such as that occurring in obesity, and calcium channel blockers, such as NF, may induce a low active form of AMPK (p-AMPK), thereby reducing energy production.…”
Section: Discussionmentioning
confidence: 99%
“…These actions were enough to block allergic inflammation. Spilanthol (3 µM to 100 µM) was also found to reduce inflammatory response by downregulating MAPK signaling pathways in 3T3-L1 pre-adipocytes [ 69 ]. Literature shows that obesity-induced chronic low-grade inflammation could lead to the development of various metabolic diseases.…”
Section: Anti-inflammatory Effects Of S Acmellamentioning
confidence: 99%
“…Huang et al [ 69 ] demonstrated that spilanthol (5 mg/kg and 10 mg/kg) might help in preventing pre-adipocyte inflammatory responses to reduce obesity-related metabolic diseases. Spilanthol significantly suppressed inflammatory mediator COX-2, promoted anti-inflammatory protein heme oxygenase-1 (HO-1) expression, and blocked the phosphorylation of c-Jun N-terminal kinase (JNK), as well as P38 protein in LPS-stimulated murine pre-adipocytes.…”
Section: Anti-inflammatory Effects Of S Acmellamentioning
confidence: 99%
“…Similarly, a polymorphism at FTO rs9939609 is significantly associated with hyperlipidemia, obesity, and insulin metabolism, and this association is mediated by target tissue receptors. Moreover, activation of the SIRT-AMPK signaling pathway reduces the expression of fatty acid synthases and associated transcription factors, increases the oxidation rate of fatty acids, and regulates lipid and energy metabolism [17][18][19].…”
Section: Discussionmentioning
confidence: 99%